Common fixed point theorems for weakly compatible non-self mappings in metric spaces of hyperbolic type - Eke, Kanayo (Global Journal of Mathematical Analysis, 2016)
In this paper, we establish common fixed point theorems for a pair of weakly compatible nonself mappingsÂ  satisfying generalized contractiveÂ  conditions in metric space of hyperbolic type. The results generalize and extend some results in literature.